Shaping zinc protoporphyrin formation during fermentation of Weissella viridescens JX11-inoculated minced meat: roles of NaCl concentration and fermentation temperature - Runze Wu; Xin Li; Qian Chen; Fangda Sun; Haotian Liu; Qian Liu; Chao Zhang; Baohua Kong (Food Bioscience, 2026)

An IDA peptide from Boea hygrometrica enhances desiccation tolerance but lacks activity in Arabidopsis - Ling Tang; Xiaohua Wang; Yuxi Wang; Xiuxiu Chen; Yuanyuan Wang; Xuanyang Wu; Runze Sun; Xin Deng (Planta, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Effects of different elevations on the biomass and species composition of green algae on Neopyropia aquaculture ropes - Yuqing Sun; Shulin Tan; Yaoyao Lei; Weimin Yao; Bangping Deng; Mingyuan Wen; Faqing He; Runze Chen; Jie Pan; Yanfei Wang; Jianheng Zhang; Peimin He (Marine Pollution Bulletin, 2026)

Unraveling the stability of fish collagen: A review of assembly mechanisms, decisive factors, and regulatory strategies from natural tissues to in vitro gels - Li Xu; Edward; Xiangpu Li; Ran Zhao; Runze Yuan; Cuixia Sun; Yiguo Zhao; Yapeng Fang (Food Research International, 2026)

A novel thermostable and glucose tolerant β-glucosidase from Caldibacillus thermoamylovorans MB12B for efficient hydrolysis of lignocellulosic biomass - Longlin Meng; Yongxuan Liu; Xiaowen Sun; Runze Ma; Xiaowei Chen; Chunjie Gong; Xun Yu (International Biodeterioration & Biodegradation, 2026)

An innovative acid treatment system for biofouling control in Neopyropia aquaculture rafts - Mingyuan Wen; Yuqing Sun; Runze Chen; Faqing He; Zehua Chen; Huanhong Ji; Lihua Xia; Yutao Qin; Peimin He; Jianheng Zhang (Marine Pollution Bulletin, 2026)

Involvement of gut microbiota in sub-chronic chlorantraniliprole-induced metabolic alteration in chironomid larvae (Propsilocerus akamusi): Evidence from multi-omics, histopathological and biochemical analysis - Zeyang Sun; Anqi Han; Jiani Li; Wei Chen; Jian Mao; Runze Li; Jian Shi; Xiaorui Yan; Chuncai Yan (Pesticide Biochemistry and Physiology, 2026)

Advances in management and disposal of construction and demolition waste containing hexabromocyclododecane: Current status and future perspectives - Sun Yingjie; Gao Chenqi; Lu Yongchao; Yan Jixian; Hong Shan; Zhu Runze; Bian Rongxing; Zhang Qingjian; Wang Yanan; Li Weihua (Journal of Environmental Chemical Engineering, 2026)

Impacts of timescales on the relationship between compound drought-hot extremes based on precipitation and groundwater - Runze Huang; Zengchao Hao; Alexander Sun; Xingyu Zhao; Yitong Zhang (Journal of Environmental Management, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

D-amino acids enhance the biocidal effect of free nitrous acid to realize sulfide control in sewers - Weiqi Zhang; Runze Li; Juntao Xia; Jianliang Sun; Zhensheng Liang; Feng Jiang (Water Research, 2026)

Fast and eco-friendly sulfidation of zero-valent iron using elemental sulfur and Geobacter sulfurreducens for groundwater remediation - Runze Li; Liang Zhang; Yanduo Yang; Weiqi Zhang; Yuming Zhen; Jianliang Sun; Feng Jiang (Water Research, 2026)

Nanoengineered polymeric RNA nanoflowers for dual-pathway modulation and effective therapy for non-small cell lung cancer - Li Wang; Dongbin Guo; Yifei Shan; Luanbiao Sun; Rong Wang; Bingmei Wang; Jiyu Guan; Quan Liu; Runze Li; Changfeng Zhu; Yicheng Zhao (Chemical Engineering Journal, 2025)

Exploring the low‐carbon development model for a hazardous waste treatment park from a life cycle assessment perspective - Chenqi Gao; Yating Niu; Xinran Du; Runze Zhu; Rongxing Bian; Ya'nan Wang; Yingjie Sun; Weihua Li; Qingjian Zhang; Huilai Chen (Journal of Industrial Ecology, 2025)
China is actively committed to mitigating carbon emissions through its “Dual Carbon” and “Zero‐Waste Cities” strategies. Hazardous waste (HW) treatment, a significant source of greenhouse gas (GHG) emissions, plays a crucial role in achieving carbon reduction targets. This study systematically assessed the carbon emissions and low‐carbon pathways of a representative multi‐HW treatment park in Qingdao using life cycle assessment and life cycle cost methodologies. In 2020, the total net GHG emissions of the HW park were 49,669.3 t CO 2 ‐eq, with an average emission intensity of 1181.1 kg CO 2 ‐eq per tonne of HW. Among the various treatment systems, medical waste (MW) incineration exhibited the highest GHG emission intensity (1377.6 kg CO 2 ‐eq/t MW), followed by industrial hazardous waste (IHW) incineration (1076.4 kg CO 2 ‐eq/t IHW), fly ash/slag treatment (9.7 kg CO 2 ‐eq/t HW), and physicochemical treatment (8.5 kg CO 2 ‐eq/t HW). Three integrated low‐carbon pathways demonstrated that utilizing waste heat for heating exhibited the highest carbon mitigation potential, achieving up to −403.6 kg CO 2 ‐eq/t IHW, followed by technological improvement and resource recycling. The combined low‐carbon scenario could achieve a 49.5% reduction in total carbon emissions compared to the baseline scenario. Furthermore, economic performance improved, with treatment benefits increasing from 3431.3 RMB/t IHW to 3948.5 RMB/t IHW due to enhanced energy efficiency and resource recovery. This study provides a framework for assessing multi‐HW parks’ carbon footprints and offers strategic insights for low‐carbon, resource‐efficient waste management. The findings also support sustainable multi‐HW management and contribute to climate and decarbonization efforts.

New insights into the effect of H2S stress on CH4 oxidation in landfill cover soils from the CH4-derived carbon allocation and its microbial mechanism - Rongxing Bian; Yating Niu; Xinran Du; Chenqi Gao; Tingxue Zhang; Runze Zhu; Yingjie Sun; Yanan Wang (Process Safety and Environmental Protection, 2025)

Permselectivity of monovalent cation exchange membrane in ampholytic electrolyte: Modeling and experiment - Xu Liu; Yixing Gou; Runze Sun; Tianyi Chen; Jingtao Bi; Bader Al-Anzi; Zirui Li (Desalination, 2025)

Machine learning-assisted rapid electromagnetic design of flexible graphene-based absorptive composites - Runze Zhang; Ye Yuan; Xiaohan Wang; Xianxian Sun; Shasha Wang; Zibo Yang; Yu Ma; Enshuang Zhang; Yibin Li (Chemical Engineering Journal, 2025)

Hormesis effect of cadmium on pakchoi growth: Unraveling the ROS-mediated IAA-sugar metabolism from multi-omics perspective - Runze Li; Mengzhan Qin; Jiyuan Yan; Tao Jia; Xiaodong Sun; Jiawen Pan; Wenwen Li; Zhiguo Liu; Mohamed A. El-Sheikh; Parvaiz Ahmad; Peng Liu (Journal of Hazardous Materials, 2025)

Efficient near-ultraviolet OLED utilizing a novel emitter based on fluorene bridge with subtlety stacking patterns - Mizhen Sun; Runze Wang; Chenglin Ma; Yannan Zhou; Xin Wang; Lizhi Chu; Wenjun Yang; Shanfeng Xue (Chemical Engineering Journal, 2025)

Integrated physiological, transcriptomic, and metabolomic investigation reveals that MgO NPs mediate the alleviation of cadmium stress in tobacco seedlings through ABA-regulated lignin synthesis - Mengzhan Qin; Jiyuan Yan; Runze Li; Tao Jia; Xiaodong Sun; Zhiguo Liu; Mohamed A. El-Sheikh; Parvaiz Ahmad; Peng Liu (Journal of Hazardous Materials, 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Identification of dehydrin family genes in three Medicago species and insights into their tolerant mechanism to salt stress - Xiuxiu Zhang; Xiuzhi Xia; Yu Sun; Runze Wang; Kemeng Liang; Yarong Wang; Lifei Ren; Qin Wang (Plant Cell Reports, 2025)

Buckling behavior analysis of corrugation reinforced composite pressure shell: Analysis of the influence of corrugation structural parameters - Runze Wu; Jianliang Sun; Xu Zhang; Cunyao Shan (Ocean Engineering, 2024)

Experimental investigation on the dynamic response of vent plate under methane-air mixtures explosion load - Runze Yu; Yanyu Qiu; Huadao Xing; Guangan Xu; Mingyang Wang; Bin Li; Lifeng Xie; Song Sun (Engineering Structures, 2024)

Responses of winter wheat yield and soil organic carbon to long-term (1990–2021) fertilization regimes under inter-annual weather variation in the Loess Plateau - Panxin Zhang; Victor O. Sadras; Runze Zhang; Lin Liu; Xueyun Yang; Benhua Sun; Changlu Hu; Hu Xu; Shulan Zhang (European Journal of Agronomy, 2024)

Comparative transcriptome analysis provides insights into the resistance regulation mechanism and inhibitory effect of fungicide phenamacril in Fusarium asiaticum - Zhitian Zheng; Huaqi Liu; Xiao Luo; Runze Liu; Alexander Dumbi Joe; Haolin Li; Haiyan Sun; Yanling Lin; Yanzhong Li; Yunpeng Wang (Pesticide Biochemistry and Physiology, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

The mechanical behavior of cylindrical shell with composite corrugations under uniform and concentrated pressure - Cunyao Shan; Jianliang Sun; Xiangteng Jia; Runze Wu; Xianghui Lu (Ocean Engineering, 2024)

Efficient and fast remediation of soil contaminated by per- and polyfluoroalkyl substances (PFAS) by high-frequency heating - Runze Sun; Samuel Babalol; Ruichong Ni; Alireza Arhami Dolatabad; Jiefei Cao; Feng Xiao (Journal of Hazardous Materials, 2024)

Specific metabolic and cellular mechanisms of the vegetative desiccation tolerance in resurrection plants for adaptation to extreme dryness - Jie Liu; Yuanyuan Wang; Xiuxiu Chen; Ling Tang; Yang Yang; Zhaolin Yang; Runze Sun; Petko Mladenov; Xiaohua Wang; Xiaoqiang Liu; Songsong Jin; Hui Li; et al. (Planta, 2024)

Influence of C/N ratio and ammonia on nitrogen removal and N2O emissions from one-stage partial denitrification coupled with anammox - Yiwen Sun; Jiashun Cao; Runze Xu; Teng Zhang; Jingyang Luo; Zhaoxia Xue; Shaofeng Chen; Shilong Wang; Hailun Zhou (Chemosphere, 2023)

Buckling performance of inner corrugated pressure shells under external hydrostatic pressure - Xu Zhang; Jianliang Sun; Runze Wu; Yan Peng (Ocean Engineering, 2023)

Effects of calcium on phosphorus recovery from wastewater by vivianite crystallization: Interaction and mechanism analysis - Jiashun Cao; Weiyi Zhao; Suna Wang; Runze Xu; Liangshan Hao; Wei Sun (Journal of Environmental Chemical Engineering, 2023)

Exosomes from Inflamed Macrophages Promote the Progression of Parkinson’s Disease by Inducing Neuroinflammation - Yan Jin; Runze Wu; Li Li; Lihua Shen; Yunjuan Gu; Cheng Sun (Molecular Neurobiology, 2023)

Recognition of aggressive behavior of group-housed pigs based on CNN-GRU hybrid model with spatio-temporal attention mechanism - Yue Gao; Kai Yan; Baisheng Dai; Hongmin Sun; Yanling Yin; Runze Liu; Weizheng Shen (Computers and Electronics in Agriculture, 2023)

Biological production of xylitol by using nonconventional microbial strains - Clarisse Manishimwe; Yifan Feng; Jingxiang Sun; Runze Pan; Yujia Jiang; Wankui Jiang; Wenming Zhang; Fengxue Xin; Min Jiang (World Journal of Microbiology and Biotechnology, 2022)

Genome-wide genetic diversity and IBD analysis reveals historic dissemination routes of pear in China - Xuening Chen; Mingyue Zhang; Manyi Sun; Yueyuan Liu; Shengnan Li; Bobo Song; Mengyan Li; Shaoling Zhang; Runze Wang; Jiaming Li; Kejiao Zhao; Jun Wu (Tree Genetics & Genomes, 2022)

Mitigation of arsenic accumulation in arugula (Eruca sativa Mill.) using Fe/Al/Zn impregnated biochar composites - Runze Sun; Jie Wang; Yutao Peng; Hongmei Wang; Qing Chen (Environmental Science and Pollution Research, 2021)

Saikosaponin C exerts anti-HBV effects by attenuating HNF1α and HNF4α expression to suppress HBV pgRNA synthesis - Yanchao Pan; Zhiyi Ke; Hong Ye; Lina Sun; Xiaoyan Ding; Yun Shen; Runze Zhang; Jing Yuan (Inflammation Research, 2019)

Formation of 1,3,8-tribromodibenzo-p-dioxin and 2,4,6,8-tetrabromodibenzofuran in the oxidation of synthetic hydroxylated polybrominated diphenyl ethers by iron and manganese oxides under dry conditions - Jiafeng Ding; Gaoyuan Long; Yang Luo; Runze Sun; Mengxia Chen; Yajun Li; Yanfang Zhou; Xinhua Xu; Weirong Zhao (Environmental Science and Pollution Research, 2018)